Cactus shaped FeOOH/Au/BiVO4 photoanodes for efficient photoelectrochemical water splitting. (14th October 2021) - Geng, Huimin; Ying, Pengzhan; Zhao, Yulong; Gu, Xiuquan
Abstract: In this work, a FeOOH/Au/BiVO4 photoanode was fabricated through dual modification with Au nanoparticles (NPs, ∼5 nm) and FeOOH nanoneedles (NNs) on nanoporous BiVO4 surface. Both the Au NPs and FeOOH NNs were distributed uniformly onto the BiVO4 by using the electrodeposition and chemisorption routes, respectively. After parameter optimization, the FeOOH/Au/BiVO4 photoanode displayed a photocurrent density of 4.64 mA cm −2 at 1.23 VRHE, which was 3.74 times higher than the pristine BiVO4 one. Besides, the FeOOH/Au/BiVO4 photoanodes also displayed a maximum H2 yield amount of 23.9 μmol cm −2  h −1 . The significantly enhanced performance could be attributed to the following reasons: Introduction of Au NPs enhanced the visible light absorption through localized surface plasmon resonance (LSPR) effect; the photo-excited "hot electrons" of Au NPs were more likely to flow into the conduction band (CB) of BiVO4 via a direct electron transfer mechanism, leading to an improvement of the charge separation/transfer efficiency; surface modification of FeOOH extracted photogenerated holes, leading to an acceleration of the surface catalytic kinetics. In a word, the present study suggests that co-sensitization of Au NPs and FeOOH might be an effective method for improving the PEC water oxidation kinetics of BiVO4 photoanodes. Highlights: FeOOH/Au/BiVO4 photoanodes were fabricated through co-modification of Au NPs and FeOOH on porous BiVO4 films. Under a bias of 1.23 VRHE, FeOOH/Au/BiVO4 displayed a photocurrent of 4.64 mA cm −2, which was 3.74 times higher than BiVO4 . H2 yield amount reaches 191.4 μmol in 2 h for the optimal FeOOH/Au/BiVO4 photoanode. Performance enhancement was attributed to improvements of both visible light harvesting and surface catalytic kinetics.